Novel Approaches to Surfactant Administration - Samir Gupta; Steven M. Donn (Critical Care Research and Practice)
Surfactant replacement therapy has been the mainstay of treatment for preterm infants with respiratory distress syndrome for more than twenty years. For the most part, surfactant is administered intratracheally, followed by mechanical ventilation. In recent years, the growing interest in noninvasive ventilation has led to novel approaches of administration. This paper will review these techniques and the associated clinical evidence.